Enhancement of emission characteristics for field emitters by N-doped hydrogen-free diamond-like-carbon coating - Kang, HK; Kim, TH; Moon, S; Jung, JH; Oh, MH (AMER INST PHYSICS, 1999)
The nitrogen-doped diamond-like-carbon (DLC) coating on the molybdenum field emitter arrays (Mo-FEAs) was reported to improve the electron emission characteristics. The plasma enhanced chemical vapor deposition method using a layer-by-layer technique was applied to deposit DLC films. Field emission characteristics were measured and the possibility of applying N-doped DLC coated emitters to high frequency vacuum devices was reported. The turn-on voltage of DLC coated FEAs was decreased from 75 to 55 V and the emission current was more stable than that of noncoated FEAs. The total transconductance of FEAs was increased and the effective work function of emitters was reduced by the N-type DLC coating. (C) 1999 American Vacuum Society. [S0734-211X(99)02101-0].
Keywords: CHEMICAL-VAPOR-DEPOSITION; ARRAY DEVELOPMENT; PLASMA; FILM; STABILITY